Case Report: Balanced Reciprocal Translocation t (17; 22) (p11.2; q11.2) and 10q23.31 Microduplication in an Infertile Male Patient Suffering From Teratozoospermia - Huang, Shan; Wu, Huiling; Qi, Yunwei; Wei, Liqiang; Lv, Xiaodan; He, Yu (Frontiers in Genetics, 2022)
Two chromosomal abnormalities are described in an infertile man suffering from teratozoospermia: balanced reciprocal translocation t(17;22) (p11.2;q11.2) and a microduplication in the region 10q23.31. Twenty genes located on the breakpoints of translocation (e.g., ALKBH5, TOP3A, SPECC1L, CDC45) are selected due to their high expression in testicular tissue, and might be influenced by chromosome translocation. Four genes located on the breakpoints of microduplication including FLJ37201, KIF20B, LINC00865, and PANK1 result in an increased dosage of genes, representing an imbalance in the genome. These genes have been reported to be associated with developmental disorders/retardation, and might be risk factors affecting spermatogenesis. Bioinformatics analysis is carried out on these key genes, intending to find the pathogenic process of reproduction in the context of the translocation and microduplication encountered in the male patient. The combination of two chromosomal abnormalities carry additional risks for gametogenesis and genomic instability, are apparently harmful to male fertility. Overall, our findings could contribute to the knowledge of male infertility caused by genetic factors.